Vicarious liability in Australia: On the move? - Goudkamp, J; Plunkett, J (Taylor and Francis, 2017)
The recent decision of the High Court of Australia in Prince Alfred College v ADC is a landmark case in the law of vicarious liability. It is the first time in almost 14 years that the High Court has grappled in earnest with the second stage of the test for vicarious liability. This note observes that Prince Alfred College charts a far more restrictive course for the vicarious liability doctrine than has been followed by UK courts. It examines the different trajectories of the law in Australia and the UK and explores possible reasons for this difference.